GOFFMAN’ DRAMATURGY OF MOVEMENT CONCEPT IN SETAN JAWA FILM BY GARIN NUGROHO - Dewi, Agustina Kusuma; Piliang, Yasraf Amir; Irfansyah, Irfansyah; Saidi, Acep Iwan (International Journal of Humanity Studies (IJHS), 2020)
Dramaturgy Goffmann closely related to the model of the interaction between the persona by assuming that a mode of social relations as a stage show. There are self-raised, there are purposely hidden for management to create a certain impression. Setan Jawa Film by Garin Nugroho, as an art film, the issue of movement as the media said the film that marks the cultural code of Java to interact. This study aims to identify the perception of motion applicable to the 'movement' in Setan Jawa Film using test questionnaire responses on the perception of respondents from diverse ethnic, which was later confirmed by the method of Focused Group Discussion with Goffmann’ Dramaturgy analysis as the basis of interpretation.